Carbon dioxide and propane nucleation: the emergence of a nucleation barrier. Issue 28 (7th July 2020) - Krohn, Jan; Lippe, Martina; Li, Chenxi; Signorell, Ruth
Abstract : A direct molecular level study of CO2 and C3 H8 nucleation indicates a transition from barrierless to barrier-limited nucleation. Abstract : We investigate homogeneous gas-phase nucleation of CO2 and C3 H8 in the uniform postnozzle flow of Laval expansions in the temperature range of 31.2 K to 62.9 K and 32.0 K to 42.1 K, respectively. Time-dependent cluster size distributions are recorded with mass spectrometry after single-photon ionization with vacuum ultraviolet light. Net monomer–cluster forward rate constants and experimental nucleation rates J are retrieved from the time-dependent cluster size distributions. The comparison of experimental enhancement factors derived from these net forward rates with calculated enhancement factors provides an indication for the transition from barrier-limited to barrierless nucleation. Our data suggest such a transition for CO2, but not for C3 H8 . The values of J lie in the range from 9 × 10 14 cm −3  s −1 to 6 × 10 15 cm −3  s −1 . For CO2, the comparison of J with a modeled nucleation rate J QM based on quantum chemical calculations of the free energy barrier also hints at a transition from barrierless condensation to barrier-limited nucleation. Furthermore, we address the influence of the carrier gas pressure on the nucleation rate.